How Important are Psychological Measures to Determine Readiness to Return to Sports after Reconstruction of the Anterior Cruciate Ligament? An Online Survey Study. - Newmarch, Tate; Betsch, Marcel; Michalik, Roman; Dwyer, Tim; Whelan, Daniel; Chahal, Jaskarndip; Theodoropoulos, John (Zeitschrift für Orthopädie und Unfallchirurgie, 2024)
BACKGROUND: Recent studies have suggested that psychological factors are important components of a successful return to sports (RTS) after anterior cruciate ligament reconstruction (ACLR). The purpose of this study was to survey physicians with respect to their criteria used to determine readiness to RTS after ACLR and to understand the significance of psychological factors on RTS. METHODS: A survey was designed to understand the practices of clinicians managing rehabilitation after ACLR, consisting of 25 questions divided into 3 different sections, including one section about psychological scores and factors affecting RTS. The survey was delivered to three North American organizations for orthopedic sports medicine. RESULTS: The total number of respondents was 113. Of the respondents, 95% considered psychological tests at least "somewhat important" (33% "important", 23% selected "very important"). Routine use of psychological tests in practice was only reported by 35% of respondents. The ACL-Return to Sport after Injury Scale was the most frequently used psychological test (23%). Fear of reinjury was considered the most common patient-cited psychological factor affecting RTS. Psychological factors ranked 8th out of 9 outcomes measures in determining readiness to RTS. CONCLUSION: This study demonstrates a discrepancy between the importance of psychological tests and the frequency of use in practice. Additional education on this topic, web-based applications, and a multidisciplinary approach may increase the usage of psychological tests to determine RTS after ACLR.
EVALuna2:525557